The devil is in the details : system solutions for equity, excellence, and student well-being - Fullan, Michael; Gallagher, Mary Jean (Thousand Oaks : Corwin, 2020)
Develop equity, excellence, and well-being across the whole system! The world is troubled! We need to combine a moral imperative and a system transformation to survive for the better. Education is crucial to our future but needs to play a more direct role in shaping our future. The Devil is in the Details shows how we can re-think the education system and its three levels of leadership-local, middle, and top-so that each level can contribute to dramatic turnaround for education and society. The focus is on examining details to ensure effective actions are taken, rather than assuming large pronouncements and policies will drive change. Readers will find: Details and analysis about successful systems in California, Ontario, and Australia Ideas for how leaders at all levels can take steps to begin Vignettes, actions and strategies that illustrate how to address equity, excellence and well-being With the goal of transforming the culture of learning to develop greater equity, excellence, and student wellbeing, this book will help you liberate the system and maintain focus.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Educational leadership